2014
DOI: 10.1017/s0033291714001809
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the dynamic network structure of the Beck Depression Inventory-II

Abstract: The network approach expands the range of depression research, making it possible to investigate the dynamic architecture of depression and opening up a whole new range of questions and analyses. Regarding clinical practice, network analyses may be used to indicate which symptoms should be targeted, and in this sense may help in setting up treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
259
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(298 citation statements)
references
References 47 publications
23
259
2
4
Order By: Relevance
“…If we spread 10 thermometers (the indicators) across a large hall and aim to measure the temperature (the latent variable), the measurements will be highly correlated because they originate from the same common cause (the reflective latent variable temperature); the correlations among thermometers are spurious and disappear once we condition on the latent variable. For depression, however, the assumption that symptom correlations are spurious is not only inconsistent with common sense (insomnia -> fatigue -> concentration problems) and residual dependencies among symptoms, but also contrasts with studies demonstrating that symptoms influence each other directly in complex dynamic systems Bringmann, Lemmens, Huibers, Borsboom, & Tuerlinckx, 2015;Fried, 2015).…”
Section: A New Perspective On Depression Sum-scoresmentioning
confidence: 91%
“…If we spread 10 thermometers (the indicators) across a large hall and aim to measure the temperature (the latent variable), the measurements will be highly correlated because they originate from the same common cause (the reflective latent variable temperature); the correlations among thermometers are spurious and disappear once we condition on the latent variable. For depression, however, the assumption that symptom correlations are spurious is not only inconsistent with common sense (insomnia -> fatigue -> concentration problems) and residual dependencies among symptoms, but also contrasts with studies demonstrating that symptoms influence each other directly in complex dynamic systems Bringmann, Lemmens, Huibers, Borsboom, & Tuerlinckx, 2015;Fried, 2015).…”
Section: A New Perspective On Depression Sum-scoresmentioning
confidence: 91%
“…Another method that can take into account temporal dependencies between the emotions of two individuals is multilevel vector-autoregressive modeling and the related random intercepts cross-lagged panel models (Bringmann et al, 2013;Bringmann, Lemmens, Huibers, Borsboom, & Tuerlinckx, 2015;Hamaker, Kuiper, & Grasman, 2015;Koval, Butler, Hollenstein, Lanteigne, & Kuppens, 2015;Randall & Butler, 2013). In addition, such models can also be studied in the frequency domain, instead of the standard time domain (Liu & Molenaar, 2016;Sadler, Ethier, Gunn, Duong, & Woody, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Network analyses recently have been applied to several mental disorders, including major depressive disorder (Bringmann, Lemmens, Huibers, Borsboom, & Tuerlinckx, 2015), posttraumatic stress disorder (McNally, Robinaugh, Wu, Wang, Deserno, & Borsboom, 2015), and substance use disorder (Rhemtulla, Fried, Aggen, Tuerlinckx, Kendler, & Borsboom, 2016). Applying network analysis to DSM-IV symptoms of substance abuse in adult twins, for instance, has indicated that using a drug more than planned was among the most central substance abuse indicators (Rhemtulla, Fried, Aggen, Tuerlinckx, Kendler, & Borsboom, 2016).…”
mentioning
confidence: 99%